Racial Differences in Ischaemia/Bleeding Risk Trade-Off during Anti-Platelet Therapy: Individual Patient Level Landmark Meta-Analysis from Seven RCTs - Kang, Jeehoon; Park, Kyung Woo; Palmerini, Tullio; Stone, Gregg W.; Lee, Michael S.; Colombo, Antonio; Chieffo, Alaide; Feres, Fausto; Abizaid, Alexandre; Bhatt, Deepak L.; Valgimigli, Marco; Hong, Myeong-Ki; Jang, Yangsoo; Gilard, Martine; Morice, Marie-Claude; Park, Duk-Woo; Park, Seung-Jung; Jeong, Young-Hoon; Park, Jiesuck; Koo, Bon-Kwon; Kim, Hyo-Soo (Thrombosis and Haemostasis, 2019)
Background Prolonged dual anti-platelet therapy (DAPT) is intended to reduce ischaemic events, at the cost of an increased bleeding risk in patients undergoing percutaneous coronary intervention (PCI). In this study, we evaluated whether race influences the ischaemia/bleeding risk trade-off.Methods We searched for randomized clinical trials (RCTs) comparing DAPT duration after PCI. To compare the benefit or harm between DAPT duration by race, individual patient-level landmark meta-analysis was performed after discontinuation of the shorter duration DAPT group in each RCT. The primary ischaemic endpoint was major adverse cardiac events (MACEs), and the primary bleeding endpoint was major bleeding events (clinicaltrials.gov NCT03338335).Results Seven RCTs including 16,518 patients (8,605 East Asians, 7,913 non-East Asians) were pooled. MACE occurred more frequently in non-East Asians (0.8% vs. 1.8%, p < 0.001), while major bleeding events occurred more frequently in East Asians (0.6% vs. 0.3%, p = 0.001). In Cox proportional hazards model, prolonged DAPT significantly increased the risk of major bleeding in East Asians (hazard ratio [HR], 2.843, 95% confidence interval [CI], 1.474–5.152, p = 0.002), but not in non-East Asians (HR, 1.375, 95% CI, 0.523–3.616, p = 0.523). East Asians had a higher median probability risk ratio of bleeding to ischaemia (0.66 vs. 0.15), and the proportion of patients with higher probability of bleeding than ischaemia was significantly higher in East Asians (32.3% vs. 0.4%, p < 0.001).Conclusion We suggest that the ischaemia/bleeding trade-off may be different between East Asians and non-East Asians. In East Asians, prolonged DAPT may have no effect in reducing the ischaemic risk, while significantly increases the bleeding risk.
Keywords: dual anti-platelet therapy; race; East Asians; ischaemia/bleeding trade-off